COMPOSITION PORTLANDSEMENT (Archive of Conferences, 2021)
Construction materials are one of the main sectors of the national economyincluding general production of construction materialscement by volume - 70%, slate - 15%, special building materials - 10% andothers - 5%. This information shows the constructionThe production of cement within the materials is of great importance and at a rapid pacedeveloping. Here we mainly tell about portland cement.